1982
DOI: 10.3758/bf03202777
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and behavioral indicants of selective attention to multifeature gratings

Abstract: The mechanisms underlying selective attention to gratings consisting of a particular conjunction of spatial frequency and orientation were investigated by means of both visual evoked potential (VEP) and behavioral measures. The effects of selective attention upon the YEP indicated two general types of selection processes: one which is specific to the features contained in the relevant gratings and is most pronounced approximately 225 msec poststimulation, and another which is specific to the conjunction of fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(47 citation statements)
references
References 17 publications
3
44
0
Order By: Relevance
“…Both Previc and Harter (1982) and Kenemans et aI. (1993) found that the SNs elicited by square-wave gratings being selected for spatial frequency and orientation showed an initial pattern ofsimple additivity, suggesting independent and parallel selection ofthe two features; at subsequent stages, however, the ERP interaction indicated that the selective processing of orientation was contingent upon the selection of spatial frequency.'…”
Section: Selection Hierarchiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Previc and Harter (1982) and Kenemans et aI. (1993) found that the SNs elicited by square-wave gratings being selected for spatial frequency and orientation showed an initial pattern ofsimple additivity, suggesting independent and parallel selection ofthe two features; at subsequent stages, however, the ERP interaction indicated that the selective processing of orientation was contingent upon the selection of spatial frequency.'…”
Section: Selection Hierarchiesmentioning
confidence: 99%
“…of attention and the ERPs associated with selectively attending to nonspatial stimulus features, such as color (Hillyard & Miinte, 1984;Wijers, Lamain, Siopsema, Mulder, & Mulder, 1989), orientation (Harter & Guido, 1980;Kenemans, Kok, & Smulders, 1993), shape (Harter et aI., 1982), or spatial frequency (Harter & Previc, 1978;Kenemans et aI., 1993;Previc & Harter, 1982). In all of these cases, the most prominent ERP component elicited by stimuli having the attended feature is a broad selection negativity (SN) that begins between 150-200 msec post stimulus and extends for another 200 msec or more.…”
mentioning
confidence: 99%
“…The onset of the Ndconj occurred at latencies much shorter than those of the termination of Nd waves associated with frequency and location features. It should also be noted that in the present experiment, unlike that of Previc and Harter (1982), Ndconj waves were extracted from ERPs to nontarget tones that did not cue responses. Thus, Nd-conj waves cannot be related to N2 and P3 components associated with target detection, or to premotor or motor potentials linked to the motor response.…”
Section: Erp Signs Of Auditory Feature Conjunctionmentioning
confidence: 99%
“…Previc and Harter (1982;see also Harter, Aine, & Schroeder, 1982) were the first to use ERP techniques to investigate feature conjunction. Subjects responded to visual targets defined by the conjunction of the orientation and spatial frequency of bar gratings (e.g., small vertical bars).…”
mentioning
confidence: 99%
“…For example, Previc and Harter (1982) found several time points in the YEP that showed amplitude differences linked to selective attention directed toward the spatial frequency and orientation of a visual stimulus. Hillyard and Miinte (1984) found a number of amplitude differences associated with selective attention to location and color.…”
mentioning
confidence: 99%